Fine-mapping of the substrate specificity of human steroid 21-hydroxylase (CYP21A2). Issue 194 (November 2019) - Stoll, Anna; Loke, Steffen; Joseph, Jan Felix; Machalz, David; de la Torre, Xavier; Botrè, Francesco; Wolber, Gerhard; Bureik, Matthias; Parr, Maria Kristina
Graphical abstract: Highlights: A-Ring structure requirements of steroidal CYP21A2 substrates were determined. Successful hydroxylation of steroids at terminal carbon of D-ring side chain requires 3-oxo group. Molecular modeling rationalizes experimental data. Pathway of metabolic generation of Oral Turinabol long-term metabolite needs reconsideration. Abstract: Cytochrome P450 enzymes (CYPs) are capable of catalyzing regio- and stereo-specific oxy functionalization reactions, which otherwise are major challenges in organic chemistry. In order to make the best possible use of these biocatalysts it is imperative to understand their specificities. Human CYP21A2 (steroid 21-hydroxylase) acts on the side-chain attached to C-17 in ring D of a steroid substrate, but the configuration of ring A also plays a prominent role in substrate cognition. Here, we comprehensively investigated this relationship using sixteen 17, 17-dimethyl-18-nor-13-ene steroids with different arrangements of hydroxy-, oxo-, fluoro- and chloro-groups and in the presence or absence of double bonds (Δ1 and/or Δ4) and heteroatoms in ring A. The results show that presence of a 3-oxo group is a strict requirement for a CYP21A2 substrate, while the other configurations tested were all tolerated. This was also confirmed by control experiments using endogenous steroids. While progesterone and 17-hydroxyprogesterone were hydroxylated at C-21, (17-hydroxy-) pregnenolone did not react. Molecular docking experiments indicate that the interaction of the carbonyl group at C-3 to the side-chain Arg234 of the enzyme is indispensable.